2008
DOI: 10.1074/jbc.m804497200
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytic Adenosine Monophosphate as an Alternative Purine Source in Plasmodium falciparum

Abstract: Plasmodium falciparum is a purine auxotroph, salvaging purines from erythrocytes for synthesis of RNA and DNA. Hypoxanthine is the key precursor for purine metabolism in Plasmodium. Inhibition of hypoxanthine-forming reactions in both erythrocytes and parasites is lethal to cultured P. falciparum. We observed that high concentrations of adenosine can rescue cultured parasites from purine nucleoside phosphorylase and adenosine deaminase blockade but not when erythrocyte adenosine kinase is also inhibited. P. fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(87 citation statements)
references
References 50 publications
1
86
0
Order By: Relevance
“…Soluble metabolites were extracted from the lysate by treatment with 0.5 M HClO 4 for 30 min on ice using published protocols (16). Samples were then neutralized with 5 M KOH and centrifuged to remove the precipitate.…”
Section: Methodsmentioning
confidence: 99%
“…Soluble metabolites were extracted from the lysate by treatment with 0.5 M HClO 4 for 30 min on ice using published protocols (16). Samples were then neutralized with 5 M KOH and centrifuged to remove the precipitate.…”
Section: Methodsmentioning
confidence: 99%
“…PfENT1 Plasmid and Site-specific Mutations-For these experiments, we used the PfENT1-pXOON plasmid containing the P. falciparum 3D7 strain pfent1 gene in the pXOON plasmid (52) that we used previously (53,16). The PfENT1-pXOON plasmid was linearized with NheI, and capped mRNA was prepared as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was demonstrated that Plasmodium falciparum is able to transport nucleotides, such as, 5 AMP from extracellular medium to inside the cell (Cassera et al, 2008). The presence of a 5 nucleotidase activity in the plasma membrane fraction 9.3-fold and 10.6-fold higher than cellular homogenate and soluble fraction, respectively ( Fig.…”
Section: Discussionmentioning
confidence: 95%